HADIS TENTANG PENCIPTAAN PEREMPUAN (TINJAUAN HADIS TAḤLĪLĪ) - Nurkholidah Nurkholidah; Tami Dewi Puspa Rahayu (UIN Siber Syekh Nurjati Cirebon, 2023)
This study is a contextual understanding of the hadith of the creation of women from ribs leading to the understanding that women are under the domination of men. This position causes women's movement and rights to be narrow and limited. This study aims to determine the understanding of the hadith with the questions: 1). What is the quality of the hadith of women created from men's ribs? 2). How should we understand the hadith of women created from men's ribs? This study is a descriptive literature study. This study found that the hadith of women created from men's ribs is a valid hadith both in terms of sanad and matan. The correct understanding of the hadith of women created from men's ribs is a contextual approach to language. The figurative meaning